2013
DOI: 10.1051/0004-6361/201322350
|View full text |Cite
|
Sign up to set email alerts
|

A hadronic scenario for HESS J1818–154

Abstract: Aims. G15.4+0.1 is a faint supernova remnant (SNR) that has recently been associated with the γ-ray source HESS J1818-154. We investigate a hadronic scenario for the production of the γ-ray emission. Methods. Molecular 13 CO (J = 1-0) taken from the Galactic Ring Survey (GRS) and neutral hydrogen (HI) data from the Southern Galactic Plane Survey (SGPS) have been used in combination with new 1420 MHz radio continuum observations carried out with the Giant Metrewave Radio Telescope (GMRT). Results. From the new … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Unfortunately, it is usually quite difficult to determine the distance precisely (Acero et al 2016). These distances are often estimated as the kinematic distance of associated molecular clouds detected via CO lines (e.g., Castelletti et al 2013), OH maser, or HI absorption features (e.g., Tian & Leahy 2011. The extinction column density of optical and/or X-ray emission and/or the dispersion measure of the associated radio pulsar can also be used to constrain the distance (e.g., Arzoumanian et al 2011).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Unfortunately, it is usually quite difficult to determine the distance precisely (Acero et al 2016). These distances are often estimated as the kinematic distance of associated molecular clouds detected via CO lines (e.g., Castelletti et al 2013), OH maser, or HI absorption features (e.g., Tian & Leahy 2011. The extinction column density of optical and/or X-ray emission and/or the dispersion measure of the associated radio pulsar can also be used to constrain the distance (e.g., Arzoumanian et al 2011).…”
Section: Model Descriptionmentioning
confidence: 99%
“…No pulsar candidates have been discovered in archival radio observations of the SNR. Castelletti et al (2013) recently discovered a molecular cloud in spatial coincidence with the northern part of the SNR shell and then suggested a hadronic origin of the TeV emission. Although this scenario cannot be excluded, the so far tentative evidence for an interaction between the MC and the shell, the poor morphological match between the MC and the TeV source, and the need to invoke an additional mechanism to explain the X-ray emission makes a hadronic scenario unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Castelletti et al (2013) placed the SNR at a distance of (4.8 ± 1.0) kpc. At this distance, the angular size of the shell of G 15.4+0.1 (12 ×18 ) corresponds to a physical size of (17 × 15) pc.…”
Section: Age and Evolution Of The Snr G 154+01 And Its Pwnmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the profiles are clearly non-gaussian, the listed parameters are only mean representative values. Additionally, we followed the procedure presented in Castelletti et al (2013) to calculate the H 2 column density of the identified molecular material and used this value, together with the corresponding distance that we derived for each cloud, to compute the total mass of the clouds. For clouds A, B, and C we assumed regions (elliptical for A, and circular for B and C) with physical sizes of approximately 2 .5 × 6 , 3 .5 and 3 in diameter, respectively.…”
Section: Distance Constraintsmentioning
confidence: 99%